Numerical analysis of the thermal comfort in a church building - Ţurcanu Florin Emilian; Verdeş Marina; Ciocan Vasilică; Burlacu Andrei; Luciu Răzvan Silviu; Bălan Marius Costel; Şosoi Gavril (E3S Web of Conferences, 2019)
Based on the monitoring campaigns, we have evaluated the indoor microclimate in a church. Most church buildings are characterised by low thermal comfort due primarily to their architecture, heating huge volume of air. The CFD tools was used for thermal comfort evaluation in case of the existing heating system during the winter season. The simulation model was validated with experimental data and it was used for thermal and air velocity profiles in the occupancy zone of churchgoers. The aim of the paper is the study the feasibility of maintaining the heritage values of the churches while achieving the significant improvement of the thermal comfort.